Optimal Length Determination for Mine Destruction using 3D Traveling Salesman Problem on a Sphere - Yilmaz, Hicran; Dogan, Sengul; Koca, Gonca Ozmen (Ieee, 2015)
In military operations, improving the efficiency and shortening the duration of the operation is intended for security by integrating weapons to unmanned systems. Unmanned vehicles are used for works that could endanger human health in defense systems, mine detection and the task of destruction. Mined land is risky to human life and destruction is costly. In this study, it is aimed to optimize cost and time in destruction of mines that have been located. Traveling Salesman Problem was used to solve the problem and three-dimensionality is based on for suitability to real-world problems. In this study, genetic algorithm method is applied to node placed randomly on a three-dimensional sphere.
Mayln Imhasi için Optimum Mesafe Tespitinde Küre Yüzeyinde 3 Boyutlu Gezgin Satici Probleminin Kullanilmasi
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: Mine Destruction; Genetic Algorithm; Travelling Salesman Problem; 3D Traveling Salesman Problem on a Sphere